2016
DOI: 10.3354/dao02986
|View full text |Cite
|
Sign up to set email alerts
|

Post-mortem findings in southern right whales Eubalaena australis at Península Valdés, Argentina, 2003-2012

Abstract: ). Postmortem examination and pathogen testing were performed on 212 whales; 208 (98.1%) were calvesof-the-year and 48.0% of these were newborns or neonates. A known or probable cause of death was established in only a small number (6.6%) of cases. These included ship strike in a juvenile and blunt trauma or lacerations (n = 5), pneumonia (n = 4), myocarditis (n = 2), meningitis (n = 1), or myocarditis and meningitis (n = 1) in calves. Ante-mortem gull parasitism was the most common gross finding. It was assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 65 publications
(93 reference statements)
2
31
0
Order By: Relevance
“…Gull harassment is considered a possible contributing factor in calf mortality ( McAloose et al, 2016). Skin wounds can vary in size from small, focal lesions covering approximately 0.1% of the dorsal back surface to large, coalescing wounds over 8% of the dorsal body wall.…”
Section: Traumamentioning
confidence: 99%
“…Gull harassment is considered a possible contributing factor in calf mortality ( McAloose et al, 2016). Skin wounds can vary in size from small, focal lesions covering approximately 0.1% of the dorsal back surface to large, coalescing wounds over 8% of the dorsal body wall.…”
Section: Traumamentioning
confidence: 99%
“…In the South Atlantic Ocean, the only evidence of Brucella in cetaceans was the detection of Brucella sp. by polymerase chain reaction (PCR) in lung tissue of a newborn female southern right whale (Eubalaena australis) stranded in Pen ınsula Vald es (Argentina) in 2003, presenting interstitial pneumonia and aspirated squames (McAloose et al, 2016). We present the first evidence of Brucella sp.…”
mentioning
confidence: 93%
“…To date, B. ceti has been identified (isolation and/or by molecular analysis) in at least 12 cetacean species from six different families (Hern andez-Mora, Palacios-Alfaro, & Gonz alez-Barrientos, 2013;McAloose et al, 2016;West et al, 2014), and seropositivity has been found in at least 35 cetacean species (Hern andez-Mora et al, 2013). Among B. ceti strains, the ST27 has been associated with human neurobrucellosis and spinal osteomyelitis after consumption of raw seafood in the Pacific Ocean (McDonald et al, 2006;Sohn et al, 2003;Whatmore et al, 2008).…”
mentioning
confidence: 99%
“…, McAloose et al . ). A variety of techniques have been used to survey the Península Valdés population including: aerial surveys conducted annually since 1971 to photo‐identify the individual whales present in the area (Payne ); aerial annual censuses to record the population abundance since 1999 (Crespo et al .…”
mentioning
confidence: 97%
“…The deaths peaked in 2012 with 113 dead calves (Rowntree et al 2013, Sironi et al 2018. The estimated age of dead calves ranged from 1 d to 4-6 mo (Rowntree et al 2013, McAloose et al 2016. A variety of techniques have been used to survey the Península Valdés population including: aerial surveys conducted annually since 1971 to photo-identify the individual whales present in the area (Payne 1986); aerial annual censuses to record the population abundance since 1999 (Crespo et al 2015); monthly land and aerial surveys to locate and then necropsy dead whales on the beach since 2003 (Rowntree et al 2013).…”
mentioning
confidence: 99%